Swedish active labour market programmes in the 1990s: Overall effectiveness and differential performance - Barbara Sianesi (Institute for Fiscal Studies (IFS), 2002)
The 'Swedish model' of active labour market programmes is investigated in relation to some crucial institutional features with two aims: examining how successful it has been in the context of the high unemployment atypically experienced by Sweden in the 1990s and trying to derive some general lessons as to which type of programme works best. The effectiveness of the programmes in improving the labour market prospects of unemployed participants is assessed in terms of their impact on individual employment probability and collection of unemployment benefits over time. The evidence as to the overall effectiveness of the programmes is rather mixed, with individuals joining a programme subsequently enjoying higher employment rates but also a higher probability of drawing unemployment benefits over time than if they had searched longer in open unemployment. The renewed eligibility to unemployment compensation following participation in a programme appears to be a most critical driving force behind these results. In fact, when comparing the programme effects for individuals entitled to unemployment benefits to the programme effects for non-entitled individuals, the positive effect on participants' employment prospects disappears, being instead replaced by a much higher probability of benefit collection. Still, the various programmes may have differential effects, making it interesting to quantify the relative performance of the six main types of Swedish programmes that were available to adult unemployed workers en Titled to unemployment benefits in the 1990s: labour market training, workplace introduction, work experience placement, relief work, trainee replacement and employment subsidies. The best performer is by far employment subsidies, followed by trainee replacement. The main finding that those programmes most similar to regular employment rank unambiguously highest has however to be appraised in the light of the macroeconomic literature, which has documented large and negative displacement and dead-weight effects exactly for these types of programme.
Keywords: C14; J38; J65; J68; 330; Active labour market programmes; unemployment insurance; evaluation; matching; treatment effects; Arbeitsmarktpolitik; Bewertung; Schweden